The Application of Teethan Electromyographic Analysis in Patients with Temporomandibular Disorders - Khomiak Катерина; Kostiuk Тетяна (Actual Dentistry, 2026)
Abstract. Temporomandibular disorders (TMD) are currently among the most common maxillofacial pathologies, affecting between 79.0% and 82.9% of the population, with a tendency toward further increase. An early clinical symptom of the condition is impaired masticatory function. The aim of the study was to investigate and perform a comparative analysis of the nature and degree of changes in the electromyographic activity and synchronization of the masticatory muscles, according to the occlusal relationships of the jaws in patients with temporomandibular disorders. Materials and Methods. Over a six-month period, 42 patients with temporomandibular disorders (TMD) of muscular and articular origin were examined. Based on their clinical manifestations and the severity of dysfunctional changes, the patients were divided into three clinical study groups. To perform a comparative analysis of the electromyographic activity and synchronization of the masticatory muscles, a specialized Teethan examination was utilized. The system allows for the evaluation of muscle apparatus symmetry via the integral Global Occlusal Balancing Index, which is presented in the form of a pie chart. During the diagnostics, key indices of occluso-muscular interaction were analyzed, including POC, BAR, TORS, IMPACT, and ASYM. The objective of this methodology was to detect functional imbalance within the occluso-muscular complex. The study enabled the determination of the degree to which specific muscle pairs influence the overall stability of the system. Results and Conclusions. The conducted study provided a comprehensive evaluation of the patients’ occluso-muscular balance. The obtained data became a key element in the diagnostics of TMD, as they allowed for the localization of compression zones and elucidated the probable pathogenetic mechanisms of the disorder’s development. The quantitative values of each analyzed index, expressed as percentages, are presented in Table 2. Analysis of the total neuromuscular balance index revealed the presence of pronounced occluso-muscular disorders in patients across all clinical study groups. Specifically, the overall balance status in Clinical Group I (CG I) ranged from 66.9% to 68.9%, in CG II from 58.7% to 61.3%, and the lowest values were recorded in CG III, spanning 55.5% to 57.4%. The integral assessment of these relationships in patients with TMD, combined with the subsequent correlation of the obtained data with occlusal contact analysis, demonstrated a full correlation between muscle activity and occlusal status. These results established a foundation for the subsequent development and implementation of a personalized treatment plan.